In the land of war canoes [videorecording (VHS)] : Kwakiutl Indian life on the Northwest coast - Curtis, Edward S., 1868-1952 (Age of exploration (Milestone Film & Video), 1992)
A saga of Kwakiutl Indian life on the northwest coast of America filmed in the summer of 1914 by Edward S. Curtis. Lost for many years, the film was finally rediscovered. In 1972 it was restored and authentic music and chants were added. It presents a fictional story of love, war and death with a basis in Kwakiutl legend and rituals.